Detecting cells with low RNA content colonizing artworks non-invasively: RNA-FISH. - Vieira, Ricardo (2017)
Various non-invasive RNA-FISH methodologies were tested in this work. They seem to be good alternatives for analyzing the potential biodeteriogenic microorganisms thriving in CH objects.